Exploitation of Ultrahigh-Performance Fibre-Reinforced Concrete for the Strengthening of Concrete Structural Members - Mohammed A. Al-Osta (Advances in Civil Engineering)
The repair and strengthening of reinforced concrete members are very important due to several factors, including unexpected increases in load levels and/or the damaging impact of aggressive environmental conditions on structural concrete members. Many researchers have turned to using materials for the repair and strengthening of damaged structures or the construction of new concrete structural members. Ultrahigh-performance fibre-reinforced concrete (UHPFRC), characterized by superior structural and durability performance in aggressive environmental conditions, is one of the materials that have been considered for the repair and strengthening of concrete structural members. The repair or strengthening of concrete structures using UHPFRC needs a thorough knowledge of the behaviour of both the strengthening material and the strengthened concrete structure at service load conditions, in addition to an understanding of the design guidelines governing the use of such materials for effective repair and strengthening. In this study, the recent issues and findings regarding the use of UHPFRC as a repair or strengthening material for concrete structural members are reviewed, analysed, and discussed. In addition, recommendations were made concerning areas where future attention and research on the use of UHPFRC as a strengthening material needs to be focused if the material is to be applied in practice.